KARAKTERISASI DAN PEMANFAATAN ASAP CAIR DARI TEMPURUNG BUAH BINTARO ( Carbera manghas Linn.) SEBAGAI KOAGULAN GETAH KARET - Djeni Hendra; Totok K Waluyo; Arya Sokanandi (Jurnal Penelitian Hasil Hutan, 2025)
Smoke liquid is a condensation product of raw material combustion containing cellulose, hemicellulose and lignin. It produces many compounds that have antimicrobial, antibacterial, and antioxidant effect such as organic acids and its derivatives. Bintaro fruit shell is a waste of oil processing bintaro that are not utilized. Generally, latex coagulation uses formic acid or acetic acid that it’s expensive and less environmentally friendly. Bintaro shell pieces is unused material and containing cellulose, hemicellulose, and lignin made into smoke liquid that is acidic and could reduce pH so the latex will coagulate faster. The purpose of this study was to use smoke liquid of shell bintaro fruit shell as an alternative coagulant for rubber latex material. Smoke liquid wasmade using a modified drum kiln with a temperature of 400 C for 7 hours. Smoke liquid is purified by distillation up to 200 C. Smoke liquid that has been purified, further analyzed of its physical properties such as water content, viscosity, specific gravity, pH, acidity and phenol. Application of smoke liquid as rubber coagulant where done using smoke liquid concentration of 5%, 10%, 15%, 20%, while smoke liquid from coconut shell was used as a comparison. The results showed that the best results for coagulating was obtained from bintaro shell concentration of 20% and the fastest time for coagulating obtained from coconut shell smoke liquid concentration of 5%. Bintaro shell smoke liquid can be used as a rubber coagulant but for coagulation time isnot as fast as coconut shell smoke liquid.